PENGEMBANGANaBAHAN AJAR SENI RUPA BERBASIS ELEARNING DENGAN MENGGUNAKAN WORDPRESSaUNTUK SISWA KELAS VIII SMP NEGERI 2 GUNUNG TALANG - Lira Afri Yulia; Suib Awrus (Serupa The Journal of Art Education, 2021)
This research aims to produce art teaching materials based on e-learning using wordpress that is valid and practical. The development model used is a 4-D model which consists of defining (defining), designing (designing), developing (developing), and distributing (disseminating). This research was only conducted until the development stage due to time constraints. This e-learning-based teaching material has been revised based on suggestions and comments from expert validators consisting of 4 art lecturers, 1 language lecturer, and 1 cultural arts teacher. E-learning based teaching materials are developed using wordpress. This development was carried out with a small-scale test consisting of 10 class VIII students of SMPN 2 Gunung Talang. The validation results obtained from the validation sheet given to the validator were with an average of 91.25% which was stated to be very valid. And the practicality test results given to students were stated to be very practical with an average of 82.7%. Based on the results obtained, it can be said that e-learning based teaching materials on model materials and illustration images are valid and practical.